2013
DOI: 10.1186/1747-597x-8-31
|View full text |Cite
|
Sign up to set email alerts
|

Brief intervention and decrease of alcohol consumption among women: a systematic review

Abstract: Problems related to alcohol consumption are priority public health issues worldwide and may compromise women’s health. The early detection of risky alcohol consumption combined with a brief intervention (BI) has shown promising results in prevention for different populations. The aim of this study was to examine data from recent scientific publications on the use of BI toward reducing alcohol consumption among women through a systematic review. Electronic searches were conducted using Web of Science, PubMed(Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…(10,14,15) As regards religion, there was a significant percentage of Catholics and Evangelicals; these data are shown in the 2010 Brazilian census and other studies about the Brazilian population profile. (16) The association between female sex and higher consumption of alcohol is in line with national and international studies (3,(17)(18)(19) that described the global increase in alcohol consumption among women in the last few years. The national survey about alcohol consumption patterns in the Brazilian population identified that young women make up the group with highest indexes of increase in alcohol consumption, and are in higher risk of presenting harmful consumption.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…(10,14,15) As regards religion, there was a significant percentage of Catholics and Evangelicals; these data are shown in the 2010 Brazilian census and other studies about the Brazilian population profile. (16) The association between female sex and higher consumption of alcohol is in line with national and international studies (3,(17)(18)(19) that described the global increase in alcohol consumption among women in the last few years. The national survey about alcohol consumption patterns in the Brazilian population identified that young women make up the group with highest indexes of increase in alcohol consumption, and are in higher risk of presenting harmful consumption.…”
Section: Discussionsupporting
confidence: 63%
“…(3) In brief, studies show universalization of consumption in relation to sex, and men cannot be thought as the main consumers. (18,19) It is worth emphasizing the importance of understanding this specific change of behavior observed among women. In order to plan intervention strategies focused on women with consumption similar of tobacco if compared to individuals who attended more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies demonstrating higher likelihood of alcohol use disorders and alcohol-related consequences among women than men at equivalent AUDIT-C scores (Rubinsky et al, 2013; Rubinsky, Kivlahan, Volk, Maynard, & Bradley, 2010). While data from randomized controlled trials that included women suggest similar efficacy of brief intervention among women and men with unhealthy alcohol use (Fleming et al, 1997; Fleming et al, 2000; Gebara et al, 2013; E. Kaner et al, 2013; Manwell et al, 2000), the efficacy of brief intervention may not extend to patients with the most severe alcohol use (Jonas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, while randomized controlled trials of brief intervention suggest similar efficacy among women and men with unhealthy alcohol use (Fleming, Barry, Manwell, Johnson, & London, 1997; Fleming et al, 2000; Gebara, Bhona, Ronzani, Lourenco, & Noto, 2013; E. Kaner et al, 2013; Manwell, Fleming, Mundt, Stauffacher, & Barry, 2000), women have been less likely than men to receive brief interventions in practice (Bertakis & Azari, 2007; Burman et al, 2004; E.…”
Section: Introductionmentioning
confidence: 99%
“…Various interventions to reduce prenatal alcohol use have been described in reviews [ 7 - 9 ]; however, only 5 studies used a randomized controlled trial to test intervention effectiveness (ie, [ 10 - 14 ]). All these interventions applied health counseling; pregnant women were screened for alcohol use and participated in motivational interviews conducted by health professionals (eg, [ 15 ]).…”
Section: Introductionmentioning
confidence: 99%